Collaborative socially responsible practices for improving the position of Chinese workers in global supply chains - Hofman, Peter S.; Wu, Bin; Liu, Kaiming (German Institute of Global and Area Studies / Leibniz-Institut für Globale und Regionale Studien, 2014)
In this paper we evaluate three projects with the participation of 40 supplier firms in several Chinese coastal provinces representing multi-stakeholder efforts to provide alternative channels through which workers can voice their concerns. The supplier firms took on these projects to reduce worker dissatisfaction and employee turnover. The projects fill an institutional void in employer–employee relations within Chinese supplier firms as they provide alternative channels for workers to voice their concerns. The role of civil society organisations focusing on labour interests was a crucial feature of the projects, through capacity-building for workers and by providing independence. The supplier firms and their workers have benefitted as firms take measures to enhance worker satisfaction, while the reduced employee turnover positively impacted firm performance. We propose that these collaborative socially responsible practices are a potential way to strengthen the positions of workers and supplier firms in global supply chains